Empirical Analysis of Mergers and Acquisitions: Evidence from International and Comparative Supply Chain Operations in Russian Market - Diana Shamilevna Usanova; Alexey Nikolaevich Kirpikov; Svetlana Sergeevna Meleshenko; Gulnara Marsovna Giniatova (International Journal of Supply Chain Management, 2019)
Fifty mergers and acquisitions deals that occurred in the period 2014-2017 in the Russian market were analyzed. Deals were randomly selected. The largest number of selected transactions accounted for 2015. 32% of all transactions occurred in the oil and gas sector of the economy. Within the framework of the study, two hypotheses were put forward: 1) the effectiveness of a merger and acquisition transaction increases with an increase in the capitalization of the company-buyer, 2) the effectiveness of a merger and acquisition transaction increases with an increase in its amount. The effectiveness of the merger and acquisition deal was expressed through the growth of the economic profit of the purchasing companies based on the comparative supply chain. Fifteen variables were selected as independent ones (return on invested capital; weighted average cost of capital; return on equity; return on assets; return on sales; multiplier â€œshare returnâ€; multiplier â€œprice / earningsâ€; multiplier â€œprice / book value of assetsâ€; multiplier â€œ business value / revenue â€; multiplierâ€œ Business cost / profit before interest, taxes and amortization â€; profitability of the company before interest, taxes and the multiplier â€œearnings before interest, taxes and depreciation / book value of assetsâ€; the dollar exchange rate, etc.), however, only two of them were included in the final type of the regression model: the price / net profit multiplier and the amount of the merger / acquisition transaction.